Keith Haring et l’héritage de la peinture américaine du XXème siècle - Hélène Gaillard (Cahiers de Narratologie)
Although Keith Haring is seen as a pioneer in the street art movement, the sources of his work are often limited to Pop Art. Yet, Haring’s street art practices do not depart from the past trends retaining instead many key aspects and principles at the core of 20th century American art. As a matter of fact, the street artist acknowledges Ashcan school leader Robert Henri — who started a trend said to be the first democratic American art—as his main influence. By observing to what extent Haring’s art echoes the preexisting American artistic values, this study will provide a new historic context to the origins of street art. It will also lead to reexamine the question of street art’s radicalism, considering the gradual evolution of its paradoxical acceptance into museums.